Pengaruh Senam terhadap Penurunan Gula Darah Puasa pada Lansia dengan Faktor Resiko Stroke - Laela Abida, Liza; Nasirudin, Yusuf (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Elderly individuals with stroke risk factors increasingly experience hyperglycemia, while structured physical activity such as low-impact aerobic exercise remains underutilized as a strategy to control fasting blood glucose levels. Objectives: This study aimed to determine the effect of aerobic exercise on fasting blood glucose reduction in elderly individuals with stroke risk factors. Methods: The research employed a quasi-experimental design with a two-group pretest-posttest approach. The study involved 20 elderly participants at Posbindu Kenanga, divided into an intervention group (aerobic exercise) and a control group (dietary education). The aerobic exercise was conducted three times a week for four weeks. Data were collected through fasting blood glucose measurements before and after the intervention using paired sample t-test and independent sample t-test. Results: This study showed that the mean fasting blood glucose level in the intervention group significantly decreased from 125.7 mg/dL to 104.4 mg/dL (p = 0.004). In contrast, the control group exhibited a slight increase from 133.9 mg/dL to 134 mg/dL (p = 0.934). The intergroup comparison revealed a p-value of 0.000, indicating a significant effect of aerobic exercise on fasting blood glucose reduction compared to the control group. Conclusions: This study concludes that aerobic exercise effectively reduces fasting blood glucose levels in elderly individuals at risk of stroke. Physical activity, such as aerobic exercise, improves insulin receptor sensitivity and enhances glucose utilization by active muscles, contributing to reduced blood glucose levels. Structured physical exercise and education are recommended as preventive strategies for managing stroke risk in elderly populations. Keywords: Aerobic exercise, Fasting blood glucose, Elderly, Stroke risk